Aktivitas Sedatif Nutrasetikal Jelly Drink Kombinasi Ekstrak Putri Malu (Mimosa Pudica Linn.) dan Ekstrak Secang (Caesalpinia Sappan L.) Sebagai Pencegah Mental Illness - Cikra Ikhda Nur Hamida Safitri; Vania Angel (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Insomnia is a sleep disorder that often occurs in teenagers. Insomnia can be treated using sedative hypnotic drugs but this can cause dangerous effects. Therefore, alternative natural ingredients are needed, such as Putri Malu and Secang, which are formulated in the form of jelly drinks as nutrasetikals. This research used 20 female mice as test animals which were divided randomly into 5 grups. The method used was the Traction Test and the data collected was the length of time the mice turned and the time the mice fell. In the positive control grup, Diazepam, distilled water and agar, the average time for mice to fall was 62.5 seconds and the time to turn around was 62.9 seconds. In the negative control grup, Jelly Drink combination of Putri Malu and Secang 0.68 g/kgBW, showed that the time for mice to fall was 106.6 seconds and the time to turn around was 128.5 seconds. In conclusion, the Jelly drink combination of Putri Malu and Secang has a sedative effect and has the potential to prevent insomnia as seen by the need for mice in the Jelly drink grup who had less time to fall and turn around.